Piaget e a teoria psicológica da aprendizagem - Rowland, Thomas; Natalicio, Luiz F. S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This paper is necessarily restricted in scope. The purpose here has been to make an initial effort to relate the dynamic theory of Piaget to a distinctive dimension of psychological science, the psychology of learning. This effort seems particularly worthwhile as psychologists become more and more involved with the education of children.